2021
DOI: 10.1007/s10479-021-03962-z
|View full text |Cite
|
Sign up to set email alerts
|

Toward the understanding of national culture in the success of non‐pharmaceutical technological interventions in mitigating COVID-19 pandemic

Abstract: This study conceptually explores the relationship between a nation’s culture and the success of utilizing various digital technologies to mitigate the spread of a pandemic, such as novel coronavirus (COVID-19). In the absence of a cure or vaccine of COVID-19, the national governments and public health authorities have been aggressively utilizing digital technologies to mitigate the pandemic spread. Given the urgency caused by COVID-19, this study highlights the importance of considering a country’s national cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 44 publications
1
42
0
3
Order By: Relevance
“…There is no doubt that in the use of non-pharmaceutical technologies [26] will also significantly depend on overcoming cultural barriers.…”
Section: Why the Need Of A Study On The Digital Dividementioning
confidence: 99%
“…There is no doubt that in the use of non-pharmaceutical technologies [26] will also significantly depend on overcoming cultural barriers.…”
Section: Why the Need Of A Study On The Digital Dividementioning
confidence: 99%
“…George et al ( 2018 ) examined the impact of the interaction between cultural values and different communication media on individuals’ ability to detect deception successfully. Moreover, a recent study has suggested that national cultural values may affect the extent to which countries utilize non-pharmaceutical technological interventions (NPTI) in mitigating the spread of coronavirus 2019 (COVID-19) pandemic (Gupta et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this vein, organizations and the whole society can benefit from a wide range of disruptive digital technologies (M. Gupta et al, 2021 ; Spanaki et al, 2021 ) to face an exceptional event like COVID-19. These include artificial intelligence (Belhadi et al, 2021 ; Fosso Wamba, Bawack, et al, 2021 ), blockchain (Dubey, Gunasekaran, Bryde, et al, 2020 ; Wamba & Queiroz, 2020 ), big data analytics (Dubey, Gunasekaran, Childe, et al, 2020 ; Fosso Wamba, Queiroz, et al, 2020 ), the internet of things (A. Sinha et al, 2019 ), 5G (Siriwardhana et al, 2020 ), 3d printing (Belhouideg, 2020 ), virtual reality (Mao et al, 2020 ), augmented reality (Sahu et al, 2020 ), digital twin applications (Ivanov & Dolgui, 2020 ), as well as the Industry 4.0 applications (Kumar & Singh, 2021 ; Queiroz, Ivanov et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%